Free-radical initiated cascade methylation or trideuteromethylation of isocyanides with dimethyl sulfoxides. Issue 62 (8th August 2017) - Zhang, Rui; Shi, Xiaoqian; Yan, Qinqin; Li, Zejiang; Wang, Zheng; Yu, Haifei; Wang, Xiaoke; Qi, Jing; Jiang, Menglu
Abstract : The methylation or trideuteromethylation reaction of isocyanides with dimethyl sulfoxides in a radical way is developed, which offers a low-cost, easy-operation cascade methylation strategy for the synthesis of phenanthridines or isoquinolines. Abstract : The methylation or trideuteromethylation reaction of isocyanides with dimethyl sulfoxides in a radical way is developed, which offers a low-cost, easy-operation cascade methylation strategy for the synthesis of phenanthridines or isoquinolines.